Advances and Barriers in Mammalian Cell Encapsulation for Treatment of Diabetes - Vos, Paul d.; Andersson, A.; Tam, S. K.; Faas, M. M.; Halle, J. P. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
Mammalian cell encapsulation is under investigation for the treatment of a wide variety of diseases, since it allows for transplantation of endocrine cells in the absence of undesired immunosuppression. The technology is based on the principle that transplanted tissue is protected for the host immune system by an artificial membrane. In spite of the simplicity of the concept, progress in the field of immuno-isolation has been hampered. During the past two decades, three major approaches of encapsulation have been studied. These include (i) intravascular macrocapsules, which are anastomosed to the vascular system as AV shunt, (ii) extravascular macrocapsules, which are mostly diffusion chambers transplanted at different sites, and (iii) extravascular microcapsules transplanted in the peritoneal cavity. The advantages and pitfalls of the three approaches are discussed and compared in view of applicability in clinical islet transplantation. At present, microcapsules, due to their spatial characteristics, offer better diffusion capacity than macrocapsules. During the past five years, important advances have been made in the knowledge of the characteristics and requirements capsules have to meet in order to provide optimal biocompatibility and survival of the enveloped tissue. Novel insight shows that islet-cells themselves and not the capsule materials should be held responsible for loss of a significant portion of the immuno-isolated islet cells and, thus, failure of the grafts on the long term. New approaches in which newly discovered inflammatory responses are silenced bring the technology of transplantation of immunoisolated cells close to clinical application.
Keywords: macroencapsulation